Generation of orthotopically functional salivary gland from embryonic stem cells. Issue 1 (December 2018) - Tanaka, Junichi; Ogawa, Miho; Hojo, Hironori; Kawashima, Yusuke; Mabuchi, Yo; Hata, Kenji; Nakamura, Shiro; Yasuhara, Rika; Takamatsu, Koki; Irié, Tarou; Fukada, Toshiyuki; Sakai, Takayoshi; et al.
Abstract Organoids generated from pluripotent stem cells are used in the development of organ replacement regenerative therapy by recapitulating the process of organogenesis. These processes are strictly regulated by morphogen signalling and transcriptional networks. However, the precise transcription factors involved in the organogenesis of exocrine glands, including salivary glands, remain unknown. Here, we identify a specific combination of two transcription factors (Sox9 and Foxc1) responsible for the differentiation of mouse embryonic stem cell-derived oral ectoderm into the salivary gland rudiment in an organoid culture system. Following orthotopic transplantation into mice whose salivary glands had been removed, the induced salivary gland rudiment not only showed a similar morphology and gene expression profile to those of the embryonic salivary gland rudiment of normal mice but also exhibited characteristics of mature salivary glands, including saliva secretion. This study suggests that exocrine glands can be induced from pluripotent stem cells for organ replacement regenerative therapy. Functional salivary glands have not been generated from embryonic stem cells (mESCs) to date. Here the authors demonstrate directed in vitro differentiation of mESCs to oral ectoderm and salivary gland rudiments that form mature, functional salivary glands after orthotopic transplantation.